2016
DOI: 10.1111/asj.12721
|View full text |Cite
|
Sign up to set email alerts
|

Body condition and stage of seasonal anestrus interact to determine the ovulatory response after male biostimulation in anovulatory Criollo × Nubian goats

Abstract: The effect of goat nutritional condition on the response to biostimulation with sexually active males during different stages of anestrus was determined. Fifty-eight Criollo × Nubian females on high and low body mass index (BMI) diets were used. Each BMI group was divided into two for biostimulation with sexually active males during May (mid-anestrus) or July (transition period). Ovulatory responses to biostimulation were characterized from serum progesterone, as well as the delay for response (first and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…During follicular development, oestradiol concentrations gradually increase concomitantly with follicle diameter (Bartlewski et al, ). In anoestrus, the number and size of antral follicles in the ovary were similar to those observed during the breeding season; however, no ovulation was observed (Ravindra & Rawlings, ; Vera‐Avila et al, ). It was also reported that the anoestrous ovary can contain follicles that reach 5 mm in diameter.…”
Section: Discussionmentioning
confidence: 60%
“…During follicular development, oestradiol concentrations gradually increase concomitantly with follicle diameter (Bartlewski et al, ). In anoestrus, the number and size of antral follicles in the ovary were similar to those observed during the breeding season; however, no ovulation was observed (Ravindra & Rawlings, ; Vera‐Avila et al, ). It was also reported that the anoestrous ovary can contain follicles that reach 5 mm in diameter.…”
Section: Discussionmentioning
confidence: 60%